EFEKTIVITAS MANDALA COLORING DALAM MENGURANGI KECEMASAN: A SYSTEMATIC REVIEW - Priwina G Pattikayhatu; Grace Houghty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Anxiety is a common psychological condition that affects emotional and physiological well-being, prompting the need for simple, accessible non-pharmacological interventions. Mandala Coloring has emerged as an art-based activity that may reduce anxiety through relaxation, focus enhancement, and emotional regulation. To summarize current empirical evidence on the effectiveness of Mandala Coloring for reducing anxiety in clinical and non-clinical populations. This systematic review followed PRISMA 2020 guidelines and applied PICOS criteria. Searches in PubMed, ScienceDirect, and SAGE Journals using “Mandala Coloring” AND “Anxiety” yielded 169 articles. Seven studies published between 2020–2025 met the inclusion criteria, consisting of randomized controlled trials and quasi-experimental designs. All included studies reported significant reductions in anxiety following Mandala Coloring interventions across various groups, including perioperative cancer patients, burn patients, hospitalized COVID-19 patients, climacteric women, veterans with PTSD, grieving students, and individuals with generalized anxiety disorder. The intervention was found to promote cognitive distraction, emotional balance, and autonomic calming. Differences in intervention duration, population characteristics, and measurement instruments contributed to variations in effect magnitude. Mandala Coloring is a low-cost, adaptable complementary therapy that effectively reduces anxiety in diverse settings. Further research incorporating physiological indicators and evaluating application in high-stress clinical environments is recommended.